The role of qualitative interviews in cognitive disorders caused by dementia: Methodological ethical challenges (part one) - Mahdi Shafiee Sabet; Fatemeh Bahramnezhad; Nahid Dehghan Nayeri (Tehran University of Medical Sciences, 2024)
According to a global report, 47 million people are currently living with dementia, and due to the aging population, its prevalence is expected to triple by 2050. In the future, Iran is expected to experience a significant increase in the elderly population. Currently, in Iran, the prevalence of dementia among individuals over 60 years old is 7.9%. Therefore, this group represents a significant population that warrants further research (1). The best understanding and explanation of human experiences come from first-hand sources, specifically from people who have experienced those phenomena. Therefore, reliable research sources place great emphasis on including the voices of these individuals (2). Qualitative research out for its collaborative, inclusive, and flexible structure, enabling the exploration of complex issues, including mixed or ambiguous attitudes (2). It can reveal the profound experiences and core values of people with cognitive impairment that may not emerge in quantitative studies. Additionally, qualitative research excels in vividly portraying these experiences and values (3). Throughout history, people with cognitive impairments have been marginalized from engagement in health and social research, resulting in their voices being inadequately represented in such studies. (2, 4). Instead, their perspectives have been channeled through their legal representatives or guardians, a practice that often entails constraints. These limitations include the inability to accurately predict the patient's decision-making process, the amount and manner of information provided, and the weight of decision-making responsibility placed on them (5). Furthermore, excluding these individuals from the research process can dehumanize them and perpetuate negative stereotypes about people with cognitive disorders. This also contributes to power imbalances (2). Therefore, it is crucial to develop strategies that ensure the safe participation of these individuals in research endeavors. Through these efforts, we can improve our understanding of policy and measures aimed at promoting health and well-being (6).